NaI(Tl+Li) scintillator as multirange energies neutron detector. (10th December 2021) - Ponomarev, D.; Filosofov, D.; Khushvaktov, J.; Lubashevskiy, A.; Rozova, I.; Rozov, S.; Shakhov, K.; Shitov, Yu.; Timkin, V.; Yakushev, E.; Zhitnikov, I.
Abstract: Novel NaIL detector (5 × 6 inch) was investigated for its neutron detection in wide energy range. It has been found that the detector together with its known ability to detect the γ-radiation it also allows to distinguish neutron signals in three quasi-independent ways. It is sensitive to neutron fluxes on a level down to 10 -3 cm -2 s -1 . In this work intrinsic α-background and neutron detection sensitivity for the NaIL detector were obtained. Experimental data was compared with results of Geant4 Monte Carlo (MC).